Hemisphere differences in response of sea surface temperature and sea ice to precession and obliquity - Wu, Zhipeng; Yin, Qiuzhen; Guo, Zhengtang; Berger, André (Global and Planetary Change, 2020)
The response of the climate system to astronomical parameters is an important scientific issue, but the internal processes and feedbacks need to be better understood. This study investigates the differences of the climate response to the astronomical forcing between the Northern (NH) and Southern (SH) hemispheres based on a more than 90,000-year long transient simulation using the model LOVECLIM. The astronomical parameters of the period 511–417 ka BP covering MIS-13, MIS-12 and MIS-11 are used, and greenhouse gases (GHG) concentrations and ice sheets are fixed, in order to investigate the role of insolation alone. Our results show that the response of sea ice and sea surface temperature (SST) to precession and obliquity is different between the two hemispheres. Precession plays a dominant role on the Arctic sea ice. This is mainly due to its response to the local summer insolation and also, to a less degree, the influence of the northward oceanic heat transport. However, obliquity plays a dominant role on the Southern Ocean sea ice through its influence on local solar radiation and also on the westerly winds. As far as the SST is concerned, it shows a strong precessional signal at low latitudes in both hemispheres. For the SST in the mid and high latitudes, obliquity plays a dominant role in the SH whereas precession is more important in the NH. This is largely due to the different response to insolation and feedbacks related to the different land-ocean distribution in the two hemispheres. Near the Equator, besides the precessional signal, the SST also shows strong half-precessional signal, which can be explained by the unique characteristics of the insolation variations at the Equator. Our results also show that during the period of low eccentricity, obliquity is more important than precession and the half-precessional signal vanishes due to reduced impact of precession, but precession is always more important in the NH than in the SH.